Analysis of Briquette Characteristics with Variations in Raw Materials of Kapok Fruit Husk (Ceiba Pentandra) and Jatropha Fruit (Ceiba Pentandra) with Starch Adhesive - Rani Husdiana; Devi Tanggasari; Samuyus Nealma (Protech Biosystems Journal, 2025)
Natural resources in Indonesia are abundant, but some are not utilized properly, resulting in environmental pollution waste, such as kapok fruit husk and jatropha fruit. This waste can be innovatively processed into briquettes. This study aims to analyze the characteristics of briquettes made from kapok fruit husk and jatropha fruit using starch adhesive. An experimental method was used with variations in raw material composition: P1=(KK 45:BJ 45:PR 10), P2=(KK 60:BJ 30:PR 10), and P3=(KK 90:PR 10). The research design applied a Completely Randomized Design (CRD) to analyze significant data at a 0.05% level. The results showed that the lowest average moisture content was at P2 with a value of 1.69%, the lowest ash content was at P2 with a value of 9.10%, the lowest volatile matter content was at P3 with a value of 84.46%, the highest fixed carbon content was at P2 with a value of 4.80%, and the highest calorific value was at P3 with a value of 9,478%. The characteristics that meet the Indonesian National Standard (SNI No.1683-2021) are only moisture content and calorific value, with the standard requiring moisture content <8-10% and calorific value >6,000. These results indicate that briquettes can serve as an environmentally friendly alternative fuel with potential for further development.